2012
DOI: 10.4161/auto.20123
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of basal autophagy reduces lung cancer cell proliferation and enhances caspase-dependent and -independent apoptosis by stimulating ROS formation

Abstract: Autophagy is a catabolic process involved in the turnover of organelles and macromolecules which, depending on conditions, may lead to cell death or preserve cell survival. We found that some lung cancer cell lines and tumor samples are characterized by increased levels of lipidated LC3. Inhibition of autophagy sensitized non-small cell lung carcinoma (NSCLC) cells to cisplatin-induced apoptosis; however, such response was attenuated in cells treated with etoposide. Inhibition of autophagy stimulated ROS forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
103
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 32 publications
9
103
2
Order By: Relevance
“…51 Furthermore, autophagy inhibition led to enhanced ROS generation in several cell lines. 52,53 Therefore, the crosstalk among ROS, ER stress, and autophagy is quite complex. Elucidating the correlation represents a major area for our future research.…”
Section: Discussionmentioning
confidence: 99%
“…51 Furthermore, autophagy inhibition led to enhanced ROS generation in several cell lines. 52,53 Therefore, the crosstalk among ROS, ER stress, and autophagy is quite complex. Elucidating the correlation represents a major area for our future research.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, pharmacological inhibition of autophagy under these conditions, particularly in combination with other chemotherapeutic agents, might lead to a favourable outcome, compromising the ability of tumour cells to adapt to stress, thus driving apoptotic-competent cells towards cell cycle arrest or programmed cell death (Carew et al, 2007;Jin et al, 2007;Maycotte and Thorburn, 2011). Other recent work suggested that suppression of autophagy leads to inhibition of cell proliferation in non-small-cell lung carcinoma (NSCLC) and sensitises cells to cisplatin-induced apoptosis by stimulation of reactive oxygen species (ROS) formation (Kaminskyy et al, 2012). By contrast, the inhibition of autophagy in apoptosis-deficient tumours, such as those overexpressing BCL2, might have detrimental effects.…”
Section: Regulation Of Autophagy By Apoptosismentioning
confidence: 99%
“…(10,15,16) However, it seems somewhat controversial that ROS is instrumental in inducing autophagy under stress conditions. (17)(18)(19)(20) In this regard, it is of interest to determine the role of ROS and autophagy in A549 cell death induced by the novel compound Pe-C.In the present study, we investigated the mechanism underlying the novel compound Pe-C in lung cancer cells. We found that Pe-C elicited autophagic cell death independent of caspase activation and apoptosis in a variety of lung cancer cells, which was mediated by the accumulation of mitochondrialderived ROS.…”
mentioning
confidence: 97%
“…(10,15,16) However, it seems somewhat controversial that ROS is instrumental in inducing autophagy under stress conditions. (17)(18)(19)(20) In this regard, it is of interest to determine the role of ROS and autophagy in A549 cell death induced by the novel compound Pe-C.…”
mentioning
confidence: 99%